Cross sections polynomial axial expansion within the APOLLO3® 3D characteristics method. (January 2022) - Gammicchia, A.; Santandrea, S.; Dulla, S.
Highlights: Introduction of a polynomial axial expansion of cross sections in the TDT neutronics lattice solver. Possibility of applying the higher-order method to depleted systems. Implementation of adapted MOC and DPN acceleration equations. Application to PWR subsystems: decisive advantage with respect to the common step-constant approach. Abstract: A polynomial expansion for cross sections has been introduced in the 3D Method Of Characteristics (MOC) solver of the APOLLO3® code, with the aim of applying the method to depleted systems. This paper addresses the suitable adaptation of the MOC equations with regards to the free and DPN -accelerated power iterations, describing also how the conceived algorithms take advantage of a vectorized implementation. An adaptive quadrature technique is presented, necessary for the evaluation of terms that, due to the polynomial description, cannot be solved analytically. The decisive advantage of the new method over a classical step-constant description of nuclear properties is assessed by comparing the results of the depletion study of a PWR assembly.